Absorbable fixation straps for laparoscopic gastropexy in dogs. (11th November 2020) - Lacitignola, Luca; Fracassi, Laura; Di Bella, Caterina; Zizzo, Nicola; Passantino, Giuseppe; Tinelli, Antonella; Crovace, Alberto Maria; Staffieri, Francesco
Abstract: Objective: To evaluate the feasibility and efficacy of laparoscopic absorbable fixation straps (AFS) for laparoscopic gastropexy in dogs. Study design: Cadaveric and prospective clinical study. Animals: Five dog cadavers for the cadaveric study; 12 dogs for the clinical study. Methods: The pyloric antrum was affixed to the abdominal wall laparoscopically by applying a series of straps. The cadaveric study assessed potential challenges during the procedure and stomach mucosal penetration. For the clinical study, the total duration of surgery, time to complete the gastropexy, and the number of straps used were recorded. Ultrasound evidence of adhesion, complications, and weight were monitored at 7, 30, and 90 days after surgery. Owner satisfaction was evaluated at the 6‐month follow‐up. Results: The total duration of surgery was 25.8 minutes (range, 19‐39; SD, 6.7), and the time to complete the gastropexy was 10.1 minutes (range, 7‐19; SD, 3.9). The linear regression analysis revealed an inverse correlation between the time to complete the gastropexy and the order of the surgeries ( r 2 = 0.75, P < .05). No complications were recorded. Ultrasound examination was used to confirm gastropexy at all follow‐ups. Conclusion: Laparoscopic gastropexy with AFS was performed in both cadavers and clinical animals with minimal complications. Persistent adhesion was demonstrated during ultrasound evaluations and in one postmortem evaluation. Clinical significance: This novel laparoscopic technique can be employed safely, effectively, and reasonably quickly, and the learning curve is expected to be relatively short.